PENGARUH PENAMBAHAN BERBAGAI KOMBINASI KONSENTRASI 2,4-DIKHLOROFENOKSIASETAT (2,4-D) DAN 6-BENSIL AMINOPURIN (BAP) PADA MEDIA MS TERHADAP TEKSTUR DAN WARNA KALUS EKSPLAN BATANG JATI (TECTONA GRANDIS LINN. F.) â€œJULâ€ - SARI, NOVITA (LenteraBio: Berkala Ilmiah Biologi, 2013)
Teak (Tectona grandis Linn. F.) "JUL" is one of the teak that the able to contribute to the supply of wood raw material. Demand of teak is increasing both at home and abroad, we need a method that could generate a lot of teak plants, rapid and uniform. One way to overcome this problem is by tissue culture techniques. Many factors influence plant growth, one of them is plant growth regulators (PGR), includes 2,4-Dikhlorofenoksiasetat (2,4-D) and 6-Benzyl Aminopurin (BAP). The purpose of this research determined the effect of PGR for textures and colours of teak trunk?s callus. The method used is the visual observation of callus. Data were analyzed by description with comparated textures and colours of callus. Callus have compact textures and different colours from each treatment.